Pengaruh Penggunaan Divine Cigarette terhadap Laju Pertumbuhan Udang Windu (Penaeus monodon) - Wiratmo, Puji; Sunaryo, Sunaryo; Yulianto, Bambang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Tiger Shrimp (P. monodon) is an important export trade commoditiy to the Indonesian economy. Optimization of tiger shrimp aquaculture products need to pay attention to environmental factors. The high level of activitis around the coastal at this time led to rise water pollutants, especially in the aquaculture area (Purba, 2012). Increased pollutants such as mercury can cause disruption of Tiger Shrimp survival The Divine Cigarette can catch, control and decay free radicals. Divine Cigarette is formulated material scavenger that is a composite of amino acids and EDTA which can capture, control and shed free radicals mercury with nanobiologi principle. The purpose of this study was to determine the effect of Divine Cigarette to the growth of Tiger Shrimp (P. monodon). This study used a completely randomized design (CRD) with 2 treatments and each were replicated 3 times. Treatment being tested was the addition of Divine Cigarette (A) and without the addition of Divine Cigarette (B) on the feed tiger shrimp (P. monodon). Observations were made on the rate of growth Tiger Shrimp (P. monodon) and statistical analysis were performed using t-test. Tiger Shrimp growth can be seen from the observation from average weight Tiger Shrimp and SGR supported several other data, ie: FE, FCR, PER and water quality parameters. Results of this study showed that treatment delivery Divine Cigarette effect on mean weight at treatment A (7,15 ± 0,53 g) higher than treatment B (6,19 ± 0,39 g) in the last week. SGR data suggest that on average in treatment A (3,72 ± 0,05 % per day) was higher than treatment B (3.03 ± 0.11% per day). Treatment with Divine Cigarette significant effect (p<0.01) to the SGR, FE, FCR and PER.